Introduction: welcoming a new editorial board - D'Ippoliti, Carlo (PSL Quarterly Review, 2014)
The brief editorial note intriduces the new issue of the journal. Starting from the current issue (March 2014), the Review has a new international editorial board. The supervisory board and Economia civile (owner of the journal) wish to thank the friends and colleagues who graciously accepted to join us in our venture. The editorial then summarizes and briefly discusses the other contributions published in this issue: by Hossein Askari and Noureddine Krichene, on Islamic finance; by Bassanetti et al., on the policy response to the economic crisis in Italy; and by Alessandro Roncaglia, reviewing the paperback edition of the photostatic reprint of the thirty-volume edition of "The Collected Writings of John Maynard Keynes". JEL codes: P43, E12, A11 Keywords: introduction, editorial, Islamic finance